Long-term outcomes in patients with acute coronary syndrome undergoing percutaneous coronary intervention without standard modifiable cardiovascular risk factors: findings from the OPT-CAD cohort - Zaixin Jiang; Haiwei Liu; Miaohan Qiu; Jing Li; Wei Zhao; Donghong Zhang; Daoshen Liu; Kun Na; Yi Li; Yaling Han (BMC Medicine)
Abstract Background Acute coronary syndrome (ACS) patients without standard modifiable cardiovascular risk factors (SMuRFs) have a higher risk of early mortality. However, little is known about their long-term outcomes, especially for patients undergoing percutaneous coronary intervention (PCI). This study aims to explore the long-term outcomes and identify independent factors associated with adverse clinical outcomes in patients with ACS undergoing PCI without SMuRFs. Methods This study used data from Optimal antiPlatelet Therapy for Chinese patients with Coronary Artery Disease (OPT-CAD) registry study. Clinical characteristics and outcomes of patients with and without SMuRFs were examined. The primary outcomes were major adverse cardia-cerebrovascular events (MACCE). The long-term (5 years) outcomes were compared between the without and with SMuRFs group in such cohort. An exploratory Cox proportional hazards regression was performed to identify the independent demographic and clinical predictors of the adverse clinical outcomes in the SMuRFs-absent cohort. Results Among 5688 patients with ACS undergoing PCI, 392 (6.9%) were in the absence of SMuRFs and 5296 (93.1%) were in the presence of SMuRFs. There were no significant differences in MACCE rates between the two cohorts (9.44% vs. 9.76%, log-rank P = 0.90). Cox proportional hazards regression indicated that age (HR, 1.06; 95% CI, 1.03–1.10; P = 0.001) and thrombus lesions (HR, 2.58; 95% CI, 1.24–5.40; P = 0.011) were independently associated with MACCE in the SMuRFs-absent cohort. Conclusions Among patients with ACS undergoing PCI, SMuRFs-absent patients had similar MACCE rates when compared with those with one or more SMuRFs at 5 years. This suggests that effective intervention strategies and updated risk assessment models are urgently needed in the SMuRFs-absent cohort. Graphical Abstract